Analisis Kejadian Ikterus Neonatorum pada Bayi di RS Hikmah Sejahtera Sukamaju Palpop Tahun 2025 - Nurma Nurma; Nilawaty Uly; Sudirman Sainuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
Neonatal jaundice is a common condition in newborns, with various factors influencing its occurrence, such as gestational age, type of delivery, maternal hemoglobin status, and maternal nutritional status. Based on preliminary observations at RS Hikmah Sejahtera Sukamaju, newborns exhibit variations in terms of gestational age, delivery type, and maternal health, which can affect the baby's health, especially in the occurrence of neonatal jaundice that may develop into physiological or pathological. This study aims to analyze the factors associated with the occurrence of neonatal jaundice in newborns at RS Hikmah Sejahtera Sukamaju. The research method employed is a quantitative study with an analytical observational design. The time approach used is cross-sectional, with the population consisting of all newborns born at RS Hikmah Sejahtera Sukamaju in 2025. Data collected includes variables of gestational age, delivery type, maternal hemoglobin status, and maternal nutritional status. The results of the study indicate that of the four variables studied, two factors significantly influenced the occurrence of neonatal jaundice: gestational age and maternal nutritional status. Meanwhile, the type of delivery and maternal hemoglobin status were found not to have a significant impact on the occurrence of neonatal jaundice in newborns at this hospital. These findings are important to enhance the understanding of factors influencing neonatal jaundice and serve as a basis for better prevention and management efforts in the hospital.